POTENSI JALAN HUTAN DALAM AKSELERASI EROSI TANAH DI KALIMANTAN BARAT - Djaban Tinambunan (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
A study on the potential of forest roads for accelerating soil erosion on was carried out at four logging companies in West Kalimantan in 1987. Road elements measured in the field are those related to the Universal Soil Loss Equation factors such as road openings, surfaces, slopes, and ditches, culverts, cuts, fills, diversion ditches, and the incidence of vegetation. The results showed that forest soil disturbances caused by road construction create ground condition which has high potentials for accelerating erosion. Factors that caused this problem, as identified in the field, are: log and steep slopes, wide ground openings, and bare soil surfaces, in addition to the originally sensitive to erosion soil type, and hot and wet weather.Further study is necessary in order to find the real amount of soil erosion occured in forest roads in West Kalimantan. Qualitatively it is known to be high but quantitatively it needs to be found